FOUNDATION AND ACTIVITIES OF THE FIRST “RUKH” CELL IN UKRAINE (1987 – 1991) - MALIARCHUK , Oleh; PALAHNIUK, Mykhailo (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the study is to elucidate, based on scientific literature, periodicals, memoirs, and archival documents, the process of creating the very first “informal” public organizations of the Ukrainian SSR in 1987 – 1991, to characterize their contribution to the creation of the NRU and state development using the example of the Ivano-Frankivsk Regional Cultural and Scientific Society “Rukh”. The research methodology is based on heuristics, reconstruction, and interpretation in order to create a holistic picture of historical events using critical analysis. The scientific novelty consists in the fact that, based on “express-information” from special issues of the socio-political centre of The Ivano-Frankivsk Regional Committee of the Communist Party of Ukraine, the memoirs and diaries of Oksana Olshanska and Oleh Maliarchuk, the process of forming the most influential socio-political organization of a new type at that time – The People's Movement of Ukraine for Perestroika (NRU, Rukh) – has been elucidated, and the experience gained in the field of national patriotic education has been highlighted. Using the example of The Ivano-Frankivsk Regional Cultural and Scientific Society “Rukh”, established de facto on December 19, 1987, and legally – on June 22, 1988, the activity process from the first cultural and educational events to political actions has been studied. Conclusions. In the history of Ukraine, the “Rukh” (NRU) embodies the Ukrainian patriotism during the collapse of the Soviet Union and the proclamation of independent states. Owing to it, we have prominent political and state figures, and leaders of local communities. The youth educated in the NRU were preparing to take up arms to fight for the independence of Ukraine and against a spiritual, occupational enslavement by russia. The forms and methods of work of “informal” organizations activists of Ukraine, tempered by generations of patriots, must develop in accordance with the challenges of today, adapt and modernize with the latest technologies. During the large-scale russian invasion of Ukraine, they fight with weapons in their hands in the ranks of the Armed Forces of Ukraine and are engaged in volunteer activities. Many Ukrainian patriots joined them, hoping to use their example and initiatives to involve as many citizens of our country as possible in building a powerful Ukrainian world as a counterweight to the “Rusky mir”. It is necessary to consolidate the Ukrainians around the national state idea in order to survive the war and build a strong state. And this will be facilitated by knowledge of history, the printed Ukrainian word, the use of the Ukrainian state language and, without any doubt, the patriotic spirit of people. In fact, from the very beginning of its creation, The Ivano-Frankivsk Regional Cultural and Scientific Society “Rukh” is a legal political organization. The main historical merit of the “Rukh” was and remains the creation of an environment for educating people in a national patriotic spirit for the realization of themselves as the Ukrainians. The historical mission has been accomplished, and our duty is to preserve the memory of the outstanding sons of Ukraine and their selfless work. Key words: national idea, revival of Ukraine, People's Movement of Ukraine (NRU), Rukh.